Active School Commuting and Sports Participation: Friends or Foes for the WHO Guidelines in Children Aged Between 3 and 7 Years (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Active school commuting (ASC) and sports participation (SP) are recognised as contributing factors in meeting WHO guidelines for physical activity (PA); however, studies in children report a consistent shortfall in meeting the recommendations. Therefore, this study aims to determine whether ASC and SP act as complementary or competing behaviours in achieving these guidelines.Methods: A sample of 279 children (5.01 ± 1.04 years) was recruited. A questionnaire was applied to their parents, in which SP and ASC were assessed as dichotomous variables (yes or no). Age-specific WHO guidelines were assessed using moderate-to-vigorous physical activity (MVPA) and total physical activity (TPA), retrieved via tri-axial accelerometer data collected for at least two weekdays and one weekend day. A binary logistic regression model was used to examine the odds ratio (OR) between the ASC and SP and the likelihood of meeting WHO guidelines, controlling for confounders (e.g. both behaviours and children’s age). A linear regression was conducted to assess the relationship between time spent in these activities. Statistical significance was set at p < 0.05.Results: Of the 279 children, more than half (n = 170, 60.9%) did not meet the guidelines. When analysing the crude OR to meet the guidelines, neither SP (β = 0.46, p = 0.082) nor ASC (β = 0.45, p = 0.155) reached statistical significance. Nonetheless, when computed together, the co-adjusted OR of meeting WHO guidelines was 1.75 times higher for those with SP than without (p = 0.042; 95% confidence interval 1.020 to 3.00). This change in OR may be explained by the inverse linear relationship observed between ASC and SP (β = –40.74, p < 0.001), suggesting a possible competing effect or behavioural compensation. This is corroborated by the low prevalence (3.9%; n = 11) of children who met the guidelines through a combination of SP and ASC. This association disappears when adjusting for categorical age (